2017
DOI: 10.1016/j.arabjc.2014.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of modified poly(Ni II -DHS) films as electrodes by the electropolymerization of Ni(II)-[5,5′-dihydroxysalen] onto indium tin oxide surface and study of their electrocatalytic behavior toward aliphatic alcohols

Abstract: Please cite this article as: A. Ourari, B. Ketfi, L. Zerroual, Elaboration of modified poly(Ni II -DHS) films as electrodes by the electropolymerization of Ni(II)-[5, 5'-dihydroxySalen] onto indium tin oxide surface and study of their electrocatalytic behavior towards aliphatic alcohols, Arabian Journal of Chemistry (2014), doi: http:// dx.Abstract Nickel (II)-DHS Complex was obtained from N,N'-bis(2,5-dihydroxybenzylidene)-1,2-diaminoethane (H 2 DHS) ligand and nickel acetate tetrahydrated in ethanolic soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In addition, the preparation procedure is usually simple, and the properties of the resulting coating can be carefully controlled. Electropolymerization has been successfully used to deform electrode surfaces with Ni(II) cyclam and similar Ni(II) tetraazamacrocyclic complexes (Ourari et al, 2017 ) or Ni(II) tetramethyldibezotetraaza(14)anulene (Ciszewski et al, 2003 ), and the resulting films showed high catalytic activity for electro-oxidation of alcohols and/or other compounds that contain OH and NH 2 . In a previous paper (Bui et al, 2019 ), polymeric metal complexes with Cu, Fe, and Ni were prepared by an AC plasma process for detecting hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the preparation procedure is usually simple, and the properties of the resulting coating can be carefully controlled. Electropolymerization has been successfully used to deform electrode surfaces with Ni(II) cyclam and similar Ni(II) tetraazamacrocyclic complexes (Ourari et al, 2017 ) or Ni(II) tetramethyldibezotetraaza(14)anulene (Ciszewski et al, 2003 ), and the resulting films showed high catalytic activity for electro-oxidation of alcohols and/or other compounds that contain OH and NH 2 . In a previous paper (Bui et al, 2019 ), polymeric metal complexes with Cu, Fe, and Ni were prepared by an AC plasma process for detecting hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%